Presse régionale et multisupports - Denis RUELLAN; Joël LANGONNE (Tic & Société)
This article retraces the path followed  by a regional daily in France in diversifying its activities and enlisting its workers in the task of mastering a multichannel journalism. It supports the hypothesis that the objective of the process is less the transformation of the traditional activities of that enterprise than the construction of a discourse of modernity and a process of acculturation of its workers to new activities that can now be developped in parallel to the production of the newspaper.